(untitled) (Academia Journal of Medicine, 2024)
Anchorage control acts as foundation of the orthodontic force system. Any undesirable movement of tooth should be controlled otherwise existing malocclusion will worsen and to prevail over this unwanted movement skeletal anchorage has been introduced in orthodontic treatment. Infrazygomatic screws are introduced to provide good anchorage control. The study was conducted to determine optimal site and angulation for placement of Infrazygomatic screw. Study includes thirty patients (15 male and 15 female) above 18 years of age. IZC bone thickness and height are measured using cone beam computed tomographic images. Theia imaging software is used for linear and angular measurement. One Way Analysis of Variance (ANOVA) test was used to determine the relation between bone thickness at different angle. Study concluded that with increase in insertion angle, infrazygomatic crest bone thickness increases. The best site for mini screw insertion in IZC is at angle of 70° in Durg population.